2004
DOI: 10.1007/s00412-004-0286-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of deletion breakpoints on chromosome 4 of Drosophila melanogaster

Abstract: As part of our effort to induce and identify mutations in all genes on chromosome 4 of Drosophila melanogaster, we have mapped the breakpoints

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…As a result, few traditional genetic reagents exist for the study of genes localized to the fourth chromosome. Although our previous chromosomal in situ results suggested that the terminal deficiency Df(4)G removed the zyx102 gene (Renfranz et al, 2003), a recent molecular study (Podemski et al, 2004) indicated that the Df(4)G breakpoint occurs just distal to zyx102. At present, there are no other known deficiencies or transposable element insertions on the fourth chromosome that affect the zyx102 gene.…”
Section: Zyx102 Knockdown Strategymentioning
confidence: 68%
“…As a result, few traditional genetic reagents exist for the study of genes localized to the fourth chromosome. Although our previous chromosomal in situ results suggested that the terminal deficiency Df(4)G removed the zyx102 gene (Renfranz et al, 2003), a recent molecular study (Podemski et al, 2004) indicated that the Df(4)G breakpoint occurs just distal to zyx102. At present, there are no other known deficiencies or transposable element insertions on the fourth chromosome that affect the zyx102 gene.…”
Section: Zyx102 Knockdown Strategymentioning
confidence: 68%
“…The first consideration is that the loss of a fourth chromosome leads to the loss of one copy of the RpS3 ribosomal protein, a Minute gene, and as such clones will be predicted to grow more slowly than surrounding tissues. As alluded to in the results section, this effect can be mitigated by a variant of FYT in which the right arm of the second chromosome contains a mutation in M(2)53 1 . In this case overall development is slowed, and clone tissues should grow faster than surrounding tissues.…”
Section: Do Not Distributementioning
confidence: 99%
“…On the X chromosome there is a heat-inducible FLP-recombinase transgene (FLP) on a yellow white background. 7 One of the second chromosomes bears a FLP-recombinase recognition target site (FRT42D) located close to the centromere of chromosome 2R, a yellow + transgene, a ubiquitous source of Gal80, and terminally, a reciprocal translocation that links all genes of the fourth chromosome to the right arm of the second chromosome (2R). [9][10][11] This chromosome is referred to as FRT Yellow Translocation (FYT).…”
Section: Do Not Distributementioning
confidence: 99%
See 2 more Smart Citations